2016
DOI: 10.1128/jcm.02971-15
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Multiplex PCR with Magnetic Resonance Detection versus Empiric or Blood Culture-Directed Therapy for Management of Suspected Candidemia

Abstract: c Candida bloodstream infections (BSI) are associated with significant morbidity, mortality, and increased health care costs. Early treatment is essential, because delayed therapy detrimentally impacts clinical outcomes. The FDA recently approved the first culture-independent direct molecular detection method for Candida BSIs (T2Candida). The speed and sensitivity of this assay give it the potential to improve patient care, but the reagents and instrumentation are expensive. We used an analytic decision tree m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 45 publications
0
31
0
1
Order By: Relevance
“…Instead, upregulation of the azole efflux pumps encoded by genes of the ATP binding cassette (ABC) or the major facilitator superfamilies (MFS) is the more important mechanism of resistance through changes in the regulation of their expression by mutations in the transcription factors, e.g., TAC1 and MRR1 (C. albicans) and CgPDR1 (C. glabrata) (Vermitsky et al, 2006;Morschhäuser et al, 2007). Candida species also have plasticity in their genomes with movement within chromosomes, which can alter both efflux pump and ERG11 expression (Perlin and Wiederhold, 2017).…”
Section: Molecular Methods To Detect Azole Resistance In Candida Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, upregulation of the azole efflux pumps encoded by genes of the ATP binding cassette (ABC) or the major facilitator superfamilies (MFS) is the more important mechanism of resistance through changes in the regulation of their expression by mutations in the transcription factors, e.g., TAC1 and MRR1 (C. albicans) and CgPDR1 (C. glabrata) (Vermitsky et al, 2006;Morschhäuser et al, 2007). Candida species also have plasticity in their genomes with movement within chromosomes, which can alter both efflux pump and ERG11 expression (Perlin and Wiederhold, 2017).…”
Section: Molecular Methods To Detect Azole Resistance In Candida Speciesmentioning
confidence: 99%
“…T2Candida was significantly more likely to be positive than cBCs (45 versus 24%, P < 0.0001) (Clancy et al, 2018). Another study found T2Candida was clinically more effective than blood culture for the management of suspected candidemia, but slightly less effective than empiric therapy (Walker et al, 2016). Prospective randomized controlled trials are required to fully evaluate the impact of the T2Candida on patient outcomes and hospital-associated costs.…”
Section: Pcr For Invasive Candidiasismentioning
confidence: 99%
“…WBC counts are typically elevated, with a prevalence of neutrophils, in cases of bacterial meningitis (Table 5). In cases of fungal, viral, and tuberculous meningitis, WBC counts may also be elevated but generally to a lesser degree than with bacterial meningitis and often in the context of lymphocytosis (70)(71)(72)(73). A detailed patient evaluation, including vaccination history, and consideration of seasonality, geography, and local epidemiology may aid in narrowing the differential diagnoses; however, microbiologic testing of CSF is generally required to establish a definitive diagnosis.…”
Section: Multiplex Detection Of Pathogens Associated With Central Nermentioning
confidence: 99%
“…Traditionally, the laboratory diagnosis of bacterial meningitis has been made by using Gram staining and culture of CSF, with molecular testing for herpes simplex virus 1 (HSV-1), HSV-2, and enterovirus, in particular, playing an important role in the diagnosis of viral CNS infections (73,74). For some causes of CNS infections, such as arboviruses, serology is considered the diagnostic method of choice.…”
Section: Multiplex Detection Of Pathogens Associated With Central Nermentioning
confidence: 99%
“…Some of these strategies include the use of PCR to detect the most common fluconazole-resistant species (i.e., C. krusei and C. glabrata) or to detect all Candida strains, regardless of species. Although another study has focused on the economics of Candida infections within the bloodstream [30], our analysis has focused on non-neutropenic patients with severe peritonitis, for the following reasons: Candida peritonitis is a major cause of invasive candidiasis in patients in ICUs [31], the use of echinocandin for this indication is off-label, and there is particular benefit for clinicians to rationalize echinocandin prescriptions in this context.…”
Section: Introductionmentioning
confidence: 99%